1 - Talking heritage: Africa at the crossroads of tradition and modernity - Tom Sanya, (African Sociological Review, 2015)
This paper address the question: given the ethical imperatives of today’s world, could traditional building heritage realistically make any fresh contributions to an alternative development model? The above questions are explored via a dialectics between the traditional earth building methods and modernity as widely understood in Uganda. Heritage is conceptualised as constitutive of interactions between processes, products and people, and the environment. The paper tests the conjecture that, claims to culture and its preservation, constitute a multi-layered veil which advertently or inadvertently obstructs Ugandans from comprehending and making the deep structural changes required to re/produce their desired architecture and lifestyles.